Identifikasi Bidang Gelincir Zona Rawan Longsor di Kawasan Wisata Puncak Taruko Kabupaten Agam Menggunakan Metode Geolistrik Resistivitas - Husnatul Fauzana; Elistia Liza Namigo (Jurnal Fisika Unand, 2024)
A research has been conducted to identify the surface of rupture plane in Puncak Taruko area, Agam Regency, West Sumatra Province using 2-dimensional resistivity geoelectric method of Wenner-Schlumberger Configuration. Data collection was carried out on three tracks with track lengths of 80, 100 and 100 m and 5 m electrode spacing. The research area is a plateau with a slope of up to 40º which is directly adjacent to the very steep cliffs of Sianok Canyon with a cliff height of 30-100m. Data processing was carried out using Res2dinv software to display a 2-dimensional image of the subsurface layer structure based on the resistivity values measured in the field. In the cross section of the mapping results in the three tracks, 4 rock layers were identified, namely clay, sand, tuff and granite. The interpretation results show that the sliding plane on each track is tuff. For Track 1 with a depth of 3,75-15,9m, for track 2 it is 5,15-19,8 m and a depth of 6,38-19,8 m for track 3. Based on the interpretation of 2D image results, the area of track 1 and 2 has a translational avalanche type and the area of track 3 has a rotational avalanche type. Based on the depth and thickness of the slide field, the greatest risk of landslide is on track 3.